PENERAPAN TAX PLANNING ATAS WITHHOLDING TAX SYSTEM TERHADAP PAJAK PENGHASILAN BADAN PADA PT. CAT - Nurwati Nurwati; Syaiful Anwar (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to analyze the Application of Tax Planning on Withholding Tax to Corporate Income Tax at PT. CAT in accordance with applicable Tax Regulations. The research method used is descriptive qualitative method. The results showed that PT. CAT has not been optimal in carrying out Tax Planning for the Withholding Tax System for Corporate Income Tax. Because it was found inefficiency to the income tax Article 21 paid as much as Rp. 53,261,874. PT. CAT has cut and collected PPh article 23 and article 4 paragraph (2) in accordance with applicable taxation provisions. Based on published data, there is no potential for Income Tax Article 23 and Article 4 paragraph (2) to be deducted / paid during 2018.